Kondisi Kualitas Air Dan Perilaku Masyarakat Di Sub Daerah Aliran Sungai (DAS) Kali Liliba Kota Kupang - Philiphi de Rosari; Ida Nurwiana; Leonardus Lewa Leko (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2020)
This research aims to; (1) to determine the water quality of Liliba River and to analyse the water quality index of Kali Liliba River using STORET (2) to identify the perceptions of various stakeholders in Kali Liliba to achieve sustainable use of water resources The study was conducted by measuring several water quality parameters such as turbidity, temperature, TDS, turbidity, smell, taste, pH, DO, ammonium, N-Nitrite, phosphate, oils and fats, hardness (CaCO3) in several sampling points and distributing questionnaires to communities living in Kali Liliba River Basin. The results showed that ammonium and phosphate concentrations in Kali Liliba had exceeded the threshold specified in accordance with Government Regulation No.82 of 2001. In addition, water quality status using STORET INDEX analysis showed that sub DAS Kali Liliba was categorized medium contaminated. The waste disposal from septic or greywater, disposal of tofu industry waste, and pig farm waste was the major contribution of water pollution in Kali Liliba.